+12h+h2+27=0

Simple and best practice solution for +12h+h2+27=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for +12h+h2+27=0 equation:



+12h+h2+27=0
We add all the numbers together, and all the variables
h^2+12h+27=0
a = 1; b = 12; c = +27;
Δ = b2-4ac
Δ = 122-4·1·27
Δ = 36
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$h_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$h_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{36}=6$
$h_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(12)-6}{2*1}=\frac{-18}{2} =-9 $
$h_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(12)+6}{2*1}=\frac{-6}{2} =-3 $

See similar equations:

| 3x+9+4x-7=21 | | 85-(14+x)=68 | | 8(c–9)=6(2c–12)-4c | | 5(x6)=100 | | 1/2x-7=3(x-4)+3 | | -4x+2(x-6)=6 | | (68-x)+16=24 | | 88=8(z+1) | | y2-16y+64=0 | | 3m−9=–3 | | 2(3x-2)=41 | | 7(y-3)+y=9 | | 2x-22=-7(x+7) | | 86-x=39 | | 6x-12+6x-12=4x+8 | | −8x−8=16 | | 6r-7=23r= | | x-67=41 | | 4v-33=-v+23 | | -8x+2(x-5)=-4 | | -3.2x+4.8-6.4x=12.6 | | 10=q-4½ | | -3(7p-7)-6(1-p)=-75 | | 47-5x=-38 | | 12=4x+56 | | 3.45=x8 | | 2(3x-1)=41 | | 5x¼-x½=6 | | 3n+24=9n | | x+14+3x-8=90 | | 1+w/8=7 | | 2(1/2q+1)=-3(2q-1)+4 |

Equations solver categories